2020
DOI: 10.1007/s40615-020-00756-0
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic: a Call to Action to Identify and Address Racial and Ethnic Disparities

Abstract: The Coronavirus disease 2019 pandemic has significantly impacted and devastated the world. As the infection spreads, the projected mortality and economic devastation are unprecedented. In particular, racial and ethnic minorities may be at a particular disadvantage as many already assume the status of a marginalized group. Black Americans have a long-standing history of disadvantage and are in a vulnerable position to experience the impact of this crisis and the myth of Black immunity to COVID-19 is detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
557
3
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(587 citation statements)
references
References 14 publications
16
557
3
11
Order By: Relevance
“…Ethnic differences in covid-19 infection are well documented. A greater susceptibility to severe disease and mortality in non-White ethnic groups has been recorded in both the US 8,9,24 and the UK. 3,5,7 We observed over two-fold increased risk of severe covid-19 in Indian/Pakistani/Bangladeshi ethnic groups and over three-fold increased risk in Black ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic differences in covid-19 infection are well documented. A greater susceptibility to severe disease and mortality in non-White ethnic groups has been recorded in both the US 8,9,24 and the UK. 3,5,7 We observed over two-fold increased risk of severe covid-19 in Indian/Pakistani/Bangladeshi ethnic groups and over three-fold increased risk in Black ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 Examination of the characteristics of people hospitalised with covid- 19 and their outcomes has given some insight into the epidemiology of the disease. [2][3][4] Reports have suggested that ethnicity 3,[5][6][7][8][9] and residential deprivation 10 are associated with death from covid-19, prompting a rapid review to be led by Public Health England. 11 There is also interest in whether use of antihypertensive medications that affect the renin-angiotensin system can increase the risk of severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) sug- were different from those we observe in the United States (Chen et al, 2020;Yu et al, 2020). Of particular concern is the Hispanic/ Latino population where significant disparities exist (Laurencin & McClinton, 2020). Symptom presentation is critical to identify early infections and for self-monitoring.…”
Section: Differences In Clinical Characteristics Of Covid-19 In Hispamentioning
confidence: 61%
“…Then, a brief description of Montana as a state is included, highlighting a series of factors that will likely be important in understanding and unpacking state‐level responses to COVID‐19 in the future. These include political climate (Bui and Sankaran 2006; Burkle and Hanfling 2015; Hahn et al 2020), state demographics (Laurencin and McClinton 2020), disaster and emergency response history (Kapucu and Van Wart 2006), as well as COVID‐19 case severity. Future work should consider questions of causation, but this preliminary case is meant to offer some insight into the proliferation of restrictions and suspension.…”
Section: Montanamentioning
confidence: 99%